KEMAMPUAN BERKOMUNIKASI SISWA MELALUI PENERAPAN MODEL STUDENT FACILITATOR AND EXPLAINING DI KELAS X SMA - Widya Rafika Sari; M Rahmad; Zuhdi Maaruf (Jurnal Pendidikan, 2019)
The purpose of this research was to determine the level of communication ability of student in class X SMA PGRI Pekanbaru, through the implementation of the Student Facilitator and Explaining model on the material of momentum and impulses. This research was conducted in class X IPA of SMA PGRI Pekanbaru in 2019, amounting to 29 students, where male students numbered 14 people while female students numbered 15 people. The research design uses a type of pre-experimental design in the form of one shot case study. The research instrument used observation sheets for oral communication ability and assessment sheets for worksheet (LKS) reports for written communication. The results of the research were obtained based on indicators of verbal communication ability which include expressing information and ideas, giving attention when others are talking, responding, and asking questions, students have the communication ability with high categories. Furthermore, students' written communication ability for each meeting have increased with an average of each indicator which includes the accuracy of the answers and the quality of writing is categorized very high. Thus it was concluded that the communication ability of students in oral and written form in class X SMA PGRI Pekanbaru can be trained to be better through the application of cooperative learning models of Student Facilitator and Explaining (SFAE) types on momentum and impulse material.